Study on Internet Banking Services of Commercial Banks in Nepal - Gautam, Sameer; Devkota, Sujan (Journal of Business and Social Sciences, 2021)
Most of the banks and financial institutions of Nepal have been moving towards the e-Banking system as all of them want to increase customer satisfaction and relationship (especially in terms of time), scope, and transaction facilities. The scope of this study is to analyze different Internet banking services and their parameters provided by commercial of Nepal. The study used a questionnaire by using Google Form, which was provided to the respondents in their email addresses for primary data collection. A sample of four respondent’s banks, from 27 banks(Nepal Rasta Bank 2021) and different 18 attributes were taken to analyze their performance. The comparative study is done by analyzing different Internet banking services and their parameters provided by commercial banks such as Transaction-Intra and Interbank, Merchant tie-up, Wallet Support, Utility payment, Transaction cost, Transaction Limit, and IPS connectivity by using bar charts analysis. The study shows that there are no single parameters that can be used to compare the services. Thus, the model of study proposed here is helpful for the comparison of services of financial institutions. Further, the model can be implemented to compare any kind of services in any service-oriented organizations.